Etika Bisnis Islam Dalam Pengelolaan Bisnis di Pesantren Mukmin Mandiri - Yogiswara Karishma W; Tika Widiastuti (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This research is aimed to determine the Islamic Business Ethics in business management at Pesantren Mukmin Mandiri Sidoarjo. Pesantren Mukmin Mandiri is one of pesantren based on agrobusiness and agro-industry which graduates entrepreneurs every year. This research used the qualitative research method and case study as the strategy. Data collection was done by interviewing and observing the research object directly. The qualitative explanatory was used as the technique of analysis by explaining the results of the interviews and of the direct observations.The results of The analysis showed that the business ethics of Islam are in some way and going well in business management in schools independent believer, it can be seen from the implementation of restrictions on the business that is concerned with the students.